Macroeconomic indicators and yield curve of Indonesian government bond - Santosa, Perdana Wahyu (Business, Management and Economics Engineering, 2021)
Purposes – Indonesian government bond (known as SUN) plays an essential role in financing sustainable development in Indonesia and is a fixed income investment vehicle that attracts foreign investors. This study aims to examine the effect of macroeconomic factors or macro-risk on the yield curve of the SUN bond. Methodology – The type of data used in this study is secondary data in the form of BI Rate, Inflation, Exchange Rate, Foreign Exchange Reserves, Current Account Deficit, and crude oil prices in the 2010–2019 period. This study used the error correction model (ECM) method. The primary sources of data are some government bodies such as the Bank Indonesia website (www.bi.go.id) and the Indonesian site Bond Market Directory (www.idx.co.id). Findings – The results showed that the exchange rate had a positive effect in the long run, while the foreign exchange reserves effect inversely on the yield curve. The BI rate, inflation rate, and oil price have a positive effect on yield significantly. Furthermore, the current account deficit has no significant impact on the yield curve for the long term and short term. Implications – There are some managerial and policy implications to maintain an efficient, fixed income market. The authorities need to promote GDP growth, pursue fiscal efficiency, keep up the credit rating and risk of current account deficit, keep a relatively low BI rate and expected inflation rate. The yield curve fluctuation is influenced by changes in some macro-monetary factors above, which should consider in making SUN investment decisions. Limitations – This study has two limitations. Firstly, the future model could use a re-specification analysis that employs the VECM method that can result in impulse response function with a shock and period study; secondly, this study could be adding some variables including budget policy and political dynamics. Originality – This study contributes to the literature by examining the yield curve using the current account deficit related to government debt and macroeconomic factors that affect the bond yield curve. These findings can arrange a strategy to develop the bond market and obtain funding with a low cost of debt funds.